Accelerated Corrosion Tests on Lapped Spliced Joints in Concrete - Eltayeb-Onsa, Sara; Abdelatif, Amged O. (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
This paper presents a new test setup of experiments to investigate corrosion at lapped spliced joints using accelerated corrosion test. The experiments were carried out on two set of samples: cylinders and beam blocks. Corrosion current readings were recorded with time and samples monitored for cracking pattern during the test. The results show that the cracks appearance and severity depend mainly on the cover diameter ratio. Also, the paper shows how the corrosion cracks propagate at lapped splice joints in concrete. The comparison of the results with previous literature was satisfactory.